(untitled) (Web of Teachers: Inderscience Research, 2025)
When exploring their surroundings (guided by educators or parents), children should not merely observe, but also examine objects, their parts and elements, perceive processes and phenomena, and reflect on them. To achieve this, the educator is tasked with employing methods such as comparison, contrast, differentiation, generalization, imitation, and other similar techniques. Additionally, during the learning process, it is important to involve older preschool children in age-appropriate types of work (cleaning small ditches, loosening soil around trees, tending to flowers).